Religion and the politicisation of sexual and gender minority rights in contemporary Africa : who’s oppressing whom? - Banda, Landilani (University of Pretoria, 2023)
Mini-Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2023.